CMOS-MEMS capacitive sensors for intra-cranial pressure monitoring : sensor fabrication & system design - George, Arup K. (2013)
Low-frequency variation of intracranial pressure (ICP) is a key indicator determining the successful outcome of a patient, subjected to traumatic brain injury (TBI). Post-trauma ICP increase can lead to fatal secondary injuries and hence continuous ICP monitoring would be an essential modality required in a neuro-monitoring system. This paper discusses the system design considerations of an integrated CMOS-MEMS sensor system for monitoring ICP in patients subjected to TBI. Design and fabrication steps of the on-chip CMOS-MEMS sensor are presented first. Interface circuit design challenges introduced by the low, not-well-controlled MEMS sensitivity and large offset due to the fabrication tolerance are discussed next. A review and comparison of the reported capacitive sensors and their interface circuits follows. The paper concludes discussing the biocompatible packaging of the system for in-vivo testing.